(3CMcGe Ydi YdGeGJ JXgQ Ydi GdeQVis - (3GHbQGW GdMcjes
(3ChdgG (B:s
(3gPG cJGH CHbQGW YGde GdjhfGfjjf GdPi hLOg ai bHQg hfbdg hJQLeg ef GdjhfGfjI Edi GdYQHjI HWQjb GdQhei EPG cGf HhLg GdeQjV hQe dG jhLO dg eSGh , hcGfJ jOg GdjSQi ehVhYI Ydi UOQg s
(3BNQgG (B:s
(3aEfg jehJ Pdc GdeQjV dEMOi YTQI djdI ef XghQ Pdc , Ch dChd djdI ef XghQgG , hYdGeJg Cf jTJgi ai eQVg PGc GdMdh TghI TOjOI JeJ s
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B4 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3WH (B(71) 7394) s
Keywords: (3GdWHs